Effects of different treatments on dewaterability of anaerobic digested sludge - Chang, Yong Wei (Nanyang Technological University, 2021)
Anaerobic digested (AD) sludge dewatering is a major challenge in wastewater treatment plant due to its high production rate and poor dewaterability. In this study, 10 AD sludge samples with various feed sources and treatment process from 4 water reclamation plants (WRP) in Singapore were used to investigate the effects of different treatments on sludge dewaterability. The sludge samples were conditioned with cationic polyelectrolyte and their dewaterability were indicated by Capillary Suction Time (CST).The physicochemical characteristics of sludge, in terms of particle size, zeta potential, and Extracellular Polymeric Substance (EPS) concentration, were analysed. CST was found to correlate with EPS concentration rather than mean particle size (D50) and zeta potential. Deterioration of sludge dewaterability generally corresponded to reduced particle size, increasing EPS concentration, and enhanced negative zeta potential. The following treatments were concluded to negatively affect sludge filterability:(1) introduction of waste activated sludge (WAS) into anaerobic digestion, (2) anaerobic co-digestion with food waste, (3)Thermal Hydrolysis Process (THP) prior to anaerobic digestion, and(4) high efficiency of anaerobic digestion. In addition, anaerobic storing of mixed AD primary sludge (PS) and AD WAS was observed to greatly improve sludge dewaterability. Thus, an appropriate storage system may be a viable approach in WRP to improve sludge dewaterability.